Snow gauge undercatch and its effect on the hydrogen and oxygen stable isotopic composition of precipitation. Issue 4 (4th July 2019) - Koehler, Geoff
ABSTRACT: We investigated the influence of post-collection changes and snow gauge undercatch on the stable isotopic compositions of winter precipitation. Post-collection changes by evaporation or sublimation can be severe, and may be minimized, but not eliminated, by emptying collection gauges immediately after snowfall. Snow gauge undercatch caused two main effects: a small direct effect caused by preferential separation of snow particles during snowfall, and a much larger effect on the measured stable isotopic compositions of average annual precipitation as a result of under representation of winter precipitation. Despite these effects, however, we found little change to calculated local meteoric water lines (LMWL) for Saskatoon, SK, Canada. A comprehensive 27-year LMWL for Saskatoon which incorporates these effects can be described by δ 2 H = 7.69 ± 0.096 × δ 18 O – 2.22 ± 1.72 ( r 2 = 0.97, n = 208).